Edukasi Kesehatan Tentang Penyakit Tidak Menular di Posbindu Desa Aneuk Paya Kecamatan Lhoknga Kabupaten Aceh Besar - Diana Lestari (ARDHI : Jurnal Pengabdian Dalam Negri, 2025)
Non-communicable diseases (NCDs), such as hypertension, diabetes mellitus, and obesity, pose significant health risks for the elderly in Indonesia, including those in Aneuk Paya Village, Lhoknga District, Aceh Besar. These conditions, if left unmanaged, can lead to severe complications, impacting the quality of life of older adults. This community service project aims to improve elderly individuals' understanding of NCDs, as well as their prevention and management, through educational initiatives carried out at the Integrated Health Post (Posbindu). The activities involved interactive counseling sessions, health assessments including blood pressure monitoring, and measurements of body weight, height, waist circumference, blood sugar, and cholesterol levels. The community service event, conducted on July 22, 2025, revealed a significant improvement in the elderly participants’ knowledge about NCDs. Notably, 83% of the participants gained a better understanding of the prevention of NCDs, while 70% reported improved knowledge regarding blood sugar and blood pressure management. Moreover, there was a noticeable increase in the number of elderly individuals attending regular Posbindu visits, which suggests a growing commitment to managing their health. Health education through Posbindu has proven to be an effective tool in raising awareness and changing health behaviors among the elderly, helping to prevent NCD complications. The project demonstrates the pivotal role of Posbindu not only in promoting NCD prevention but also in providing continuous support to the elderly in managing their health, ultimately enhancing their quality of life. This initiative highlights the importance of local health programs in addressing the growing prevalence of NCDs in elderly populations and emphasizes the need for further community-based health interventions.